One-Step Assembly of a Porcine Epidemic Diarrhea Virus Infectious cDNA Clone by Homologous Recombination in Yeast: Rapid Manipulation of Viral Genome With CRISPR/Cas9 Gene-Editing Technology - Zhou, Yanyang; Li, Chenxi; Ren, Cicheng; Hu, Jingbo; Song, Changxu; Wang, Xinjie; Li, Yanhua (Frontiers in Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV), a swine enteric coronavirus causing acute diarrhea in piglets, is one of the major threatens to the pork industry globally. Reverse genetics is a valuable tool for the virological study and vaccine development for coronaviruses. Due to the large size and unstable problem in E. coli of coronavirus genome, construction and manipulation of reverse genetics system for coronaviruses remain laborious and time-consuming. In this study, a reverse genetics system of the genotype II PEDV strain HM was generated using the transformation-associated recombination (TAR) technology in yeast within one week. The rescued virus (rPEDV) exhibited similar growth properties to the wild-type virus in vitro. With this PEDV infectious cDNA clone, CRISPR/Cas9 technology and homologous recombination were combined to generate a recombinant virus rPEDV-EGFP in which the ORF3 gene was swapped with an EGFP gene. The reporter virus displayed similar growth properties to the parental virus rPEDV and remained stable during serial passage in vitro. Of note, the strategies of construction and manipulation of PEDV infectious cDNA clone are extremely simple and efficient, which could be applied for other RNA viruses and DNA viruses.